Epithelioid Sarcoma Arising in a Long-Term Survivor of an Atypical Teratoid/Rhabdoid Tumor in a Patient With Rhabdoid Tumor Predisposition Syndrome. (April 2021) - Baker, Tiffany G; Lyons, Michael J; Leddy, Lee; Parham, David M; Welsh, Cynthia T
Rhabdoid tumor predisposition syndrome (RTPS) is defined as the presence of a SMARCB1 or SMARCA4 genetic aberration in a patient with malignant rhabdoid tumor. Patients with RTPS are more likely to present with synchronous or metachronous rhabdoid tumors. Based on the current state of rhabdoid tumor taxonomy, these diagnoses are based largely on patient demographics, anatomic location of disease, and immunohistochemistry, despite their nearly identical histologic and immunohistochemical profiles. Thus, the true distinction between such tumors remains a diagnostic challenge. Central nervous system atypical teratoid/rhabdoid tumor (AT/RT) is a rare, aggressive, primarily pediatric malignancy with variable histologic features and a well documented association with loss of SMARCB1 expression. Epithelioid sarcoma (ES) is a rare soft tissue tumor arising in patients of all ages and characteristically staining for both mesenchymal and epithelial immunohistochemical markers while usually demonstrating loss of SMARCB1 expression. To our knowledge we herein present the first documented case of a patient with RTPS who presented with metachronous AT/RT and ES.